Characteristics of US Adults Who Would Be Recommended for Lifestyle Modification Without Antihypertensive Medication to Manage Blood Pressure. (29th October 2020) - Jackson, Sandra L; Park, Soyoun; Loustalot, Fleetwood; Thompson-Paul, Angela M; Hong, Yuling; Ritchey, Matthew D
Abstract: Background: The 2017 American College of Cardiology / American Heart Association Guideline for blood pressure (BP) management newly classifies millions of Americans with elevated BP or stage 1 hypertension for recommended lifestyle modification alone (without pharmacotherapy). This study characterized these adults, including their cardiovascular disease risk factors, barriers to lifestyle modification, and healthcare access. METHODS: This cross-sectional study examined nationally representative National Health and Nutrition Examination Survey data, 2013–2016, on 10, 205 US adults aged ≥18, among whom 2, 081 had elevated BP or stage 1 hypertension and met 2017 ACC/AHA BP Guideline criteria for lifestyle modification alone. RESULTS: An estimated 22% of US adults (52 million) would be recommended for lifestyle modification alone. Among these, 58% were men, 43% had obesity, 52% had low-quality diet, 95% consumed excess sodium, 43% were physically inactive, and 8% consumed excess alcohol. Many reported attempting lifestyle changes (range: 39%–60%). Those who reported receiving health professional advice to lose weight (adjusted prevalence ratio 1.21, 95% confidence interval 1.06–1.38), reduce sodium intake (2.33, 2.00–2.72), or exercise more (1.60, 1.32–1.95) were significantly more likely to report attempting changes. However, potential barriers to lifestyle modification included 28% of adults reporting disability, asthma, or arthritis. Additionally, 20% had no health insurance and 22% had no healthcare visits in the last year. Conclusions: One-fifth of US adults met 2017 ACC/AHA BP Guideline criteria for lifestyle modification alone, and many reported attempting behavior change. However, barriers exist such as insurance gaps, limited access to care, and physical impairment. Graphical Abstract: